The Innate Immune Protein Calprotectin Interacts With and Encases Biofilm Communities of Pseudomonas aeruginosa and Staphylococcus aureus - Baishya, Jiwasmika; Everett, Jake A.; Chazin, Walter J.; Rumbaugh, Kendra P.; Wakeman, Catherine A. (Frontiers in Cellular and Infection Microbiology, 2022)
Calprotectin is a transition metal chelating protein of the innate immune response known to exert nutritional immunity upon microbial infection. It is abundantly released during inflammation and is therefore found at sites occupied by pathogens such as Pseudomonas aeruginosa and Staphylococcus aureus. The metal limitation induced by this protein has previously been shown to mediate P. aeruginosa and S. aureus co-culture. In addition to the transition metal sequestration role of calprotectin, it has also been shown to have metal-independent antimicrobial activity via direct cell contact. Therefore, we sought to assess the impact of this protein on the biofilm architecture of P. aeruginosa and S. aureus in monomicrobial and polymicrobial culture. The experiments described in this report reveal novel aspects of calprotectin’s interaction with biofilm communities of P. aeruginosa and S. aureus discovered using scanning electron microscopy and confocal laser scanning microscopy. Our results indicate that calprotectin can interact with microbial cells by stimulating encapsulation them in mesh-like structures. This physical interaction leads to compositional changes in the biofilm extracellular polymeric substance (EPS) in both P. aeruginosa and S. aureus.